2016
DOI: 10.1186/s12889-016-3822-2
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity and Redesigned Community Spaces (PARCS) Study: Protocol of a natural experiment to investigate the impact of citywide park redesign and renovation

Abstract: BackgroundThe built environment plays a critical role in promoting physical activity and health. The association between parks, as a key attribute of the built environment, and physical activity, however, remains inconclusive. This project leverages a natural experiment opportunity to assess the impact of the Community Parks Initiative (CPI), a citywide park redesign and renovation effort in New York City, on physical activity, park usage, psychosocial and mental health, and community wellbeing.MethodsThe proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Participants of the PARCS study live within the 0.3-mile buffer of each study neighborhood. The PARCS Study includes adults ≥18 years of age with no mobility issues and who understand/speak English, Spanish, or Chinese (Mandarin or Cantonese) [39]. Out of twenty participants of the current qualitative study, 17 were women, 3 were men; 5 self-identified as Hispanic or Latino/a, 6 as Black or African American, 5 as White or Caucasian, 4 as Other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants of the PARCS study live within the 0.3-mile buffer of each study neighborhood. The PARCS Study includes adults ≥18 years of age with no mobility issues and who understand/speak English, Spanish, or Chinese (Mandarin or Cantonese) [39]. Out of twenty participants of the current qualitative study, 17 were women, 3 were men; 5 self-identified as Hispanic or Latino/a, 6 as Black or African American, 5 as White or Caucasian, 4 as Other.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, this qualitative research is a sub-study of a larger research project—the PARCS (Physical Activity and Redesigned Community Spaces) Study. The PARCS study leverages a natural experiment opportunity to examine the impact of the Community Parks Initiative (CPI)—a citywide redesign and renovation effort in New York City—on physical activity, park usage, psychosocial and mental health, and community wellbeing [39]. …”
Section: Introductionmentioning
confidence: 99%
“…One study protocol was found focusing on the potential impact of refurbishment, renovation, and redesign of parks on health and well-being in New York City, USA. By using thirty intervention park neighborhoods and twenty control park neighborhoods, the study will investigate whether improvements in physical activity, park usage, psychosocial and mental health, and community well-being can be observed among residents in intervention versus control neighborhoods [26]. The same approach will be used in a study conducted in Melbourne, Australia, but is not described here in detail due to our exclusion criteria mentioned in the Methods section [57].…”
Section: Studies On Urbwellth-the Morphology Sectormentioning
confidence: 99%
“…Yet much of the available evidence on associations between neighbourhood characteristics, the PA environment and resident activity has been cross-sectional, [9,[19][20][21] and few studies [22][23][24][25][26][27] have assessed health outcomes, including PA, on the same residents both before and after a substantial change in the physical environment. Thus, it is still unclear whether self-selection biases are responsible for the significant associations between features of the environment and health outcomes, or whether there are specific neighbourhood characteristics that may lead (causally) to health or health behavior improvements.…”
Section: Introductionmentioning
confidence: 99%